KARAKTER DAN NILAI MORAL DALAM FILM SOCIAL NETWORK YANG DISUTRADARAI OLEH DAVID FINCHER - Septia Agnia; Rifari Baron (INFERENCE: Journal of English Language Teaching, 2019)
The purpose of the research is to find out 1). The main character in the film The Social Network directed by David Fincher, 2) Moral values in the film The Social Network directed by David Fincher. The method used in this research is descriptive qualitative. The technique used in this research is the literature method. The results showed: 1) The characters contained in the film "Social Network" directed by David Fincher are 50% including the characters of Mark and Aduardo who are protagonist with 5 data and antagonists with 5 data. 2) Moral Value contained in the film "Social Network" directed by David Fincher is amounting to 50%, namely the character of Mark contained moral values 1) Good learners with 3 data 2) Compassion with 2 data 3) Successful and famous with 2 data, and Eduardo contained good moral values: 1) familiar with 1 data, and 2) many relations with 2 data.